PHYTOCHEMICAL INVESTIGATION OF CHLOROFORM EXTRACT FROM ROOT, STEM AND LEAF OF ADENOCALYMMA IMPERATORIS- MAXIMILIANII (WAWRA) L.G. LOHMAM (BIGNONIACEAE) - G. G. DE OLIVEIRA,; J. A. DE S. PEREIRA JUNIOR,; I. V. G. A. BASTOS,; R. C. SAMPAIO FILHO,; N. P. LOPES,; S. J.DE MELO, (International Journal of Pharma and Bio Sciences, 2014)
The Bignoniaceae family has 110 genera and approximately 650 species, widely distributed in tropical regions. Among the genera of this family, the Adenocalymma (75 species) have been little investigated from a phytochemical point of view, found only ethnobotanical reports. The aim of this study was the phytochemical characterization of chloroform extracts from the vegetative parts (root, stem and leaves) of Adenocalymma imperatoris-maximilianii (Wawra) L.G. Lohmann using analysis by GC-MS. Seventy-one secondary metabolites were identified in chloroform extracts of the root, eleven compounds were detected in stems and seventeen were found in the leaves. There was evidence of neophytadiene in the vegetative parts of this species. Five compounds were common only to stem and leaf extracts. In the root extract, we observed compounds belonging to the alkaloid class. Due to the importance and the various biological activities described in the literature on compounds identified in this study A. imperatoris-maximilianii can be considered an alternative source of bioactive secondary metabolites for pharmaceutical therapy.